Evil corporations: law, culpability, and regulation - Crofts, Penny (Routledge, 2025)
Can capitalism ever be other than evil? / James Martel -- Can a corporation be evil? / Luke Russell -- Corporate vice / Stephanie Collins -- Ecocide, evil, and the corporation / Joanna Kyriakakis -- Prescription medicine, adverse effects, and economies of death / Marc Trabsky and Jacinthe Flore -- The corporate evil of unsafe products : strict liability, negligence, and the expressive force of law / Hui Chia and Jeannie Paterson -- Data brokers : trading on trust / Olivia Dixon -- Evil corporations in horror fiction / Penny Crofts -- Corporate office, corporate irresponsibility, and the constitutive vicariousness of corporate power / Timothy D Peters -- Blindness without a will : the dilemma of corporate collective knowledge and intention in succession / Lisa Siraganian -- Corporate misuse of legal professional privilege : concealing and constituting crimes / Liz Campbell -- The monster within : representing corporate evil / Mihailis E. Diamantis -- Corporations as haunted entities : conceptualising responsibility for historical harm / Penny Crofts and Honni van Rijswijk -- Corporate evil : a story of systems and silences / Elise Bant -- Redeeming corporations : designing legal interventions for complex adaptive systems / Rebecca Wallis and Simon Bronitt -- 'Corporate culture' is the problem, but can it be regulated? / Vicky Comino.